Epigenetic Modifications and Accumulation of DNA Double-Strand Breaks in Oral Lichen Planus Lesions Presenting Poor Response to Therapy. Issue 30 (July 2015) - Dillenburg, Caroline S.; Martins, Marco A.T.; Almeida, Luciana O.; Meurer, Luise; Squarize, Cristiane H.; Martins, Manoela D.; Castilho, Rogerio M.; Priscila, Tobouti.
<x xml:space="preserve">Abstract</x> Abstract Epigenetics refers to changes in cell characteristics that occur independently of modifications to the deoxyribonucleic acid (DNA) sequence. Alterations mediated by epigenetic mechanisms are important factors in cancer progression. Although an exciting prospect, the identification of early epigenetic markers associated with clinical outcome in premalignant and malignant disorders remains elusive. We examined alterations in chromatin acetylation in oral lichen planus (OLP) with distinct clinical behavior and compared the alterations to the levels of DNA double-strand breaks (DSBs). We analyzed 42 OLP patients, who had different responses to therapy, for acetyl-histone H3 at lys9 (H3K9ac), which is associated with enhanced transcription and nuclear decondensation, and the presence of DSBs, as determined by accumulation of phosphorylated γH2AX foci. Patients with high levels of H3K9ac acetylation failed to respond to therapy or experienced disease recurrence shortly after therapy. Similar to H3K9ac, patients who responded poorly to therapy had increased accumulation of DNA DSB, indicating genomic instability. These findings suggest that histone modifications occur in OLP, and H3K9ac and γH2AX histones may serve as epigenetic markers for OLP recurrence.